Green value and servitization effects on purchase intentions toward Indonesian micro food enterprises - Lazuardi, Yanuar; Maulidi, Ach; Ramadan Ben Galboun, Abdalmenam (Manajemen dan Bisnis, 2026)
This study is to examine the effect of Green Perceived Value (GPV) on Intention to Buy (ITB) by Green Servitization (GS) as its mediating role. This study is as a response to prior studies grounded on classical economic and rational choice theories suggesting that ITB is a direct consequence of a cost-benefit analysis. Even though we do not hypothesise green-feminine stereotype, we examine it in our additional analysis. Our findings suggest that GPV does not have a direct effect on ITB, but its influence is mediated through GS. This indirect relationship is significant in the overall analysis and for females, indicating that GS plays a crucial role in linking GPV to ITB. For females, GPV positively influences GS, which in turn significantly impacts ITB, confirming a full mediation effect. This suggests that women are more likely to translate GPV into ITB through the development of GS. However, for males, while GPV strongly influences GS, GS does not significantly affect ITB, resulting in an insignificant mediation effect. This indicates that the relationship between GPV and ITB is gender-dependent, with females demonstrating a clearer pathway where GS acts as a bridge, while for males, GS does not play the same mediating role. These results highlight the importance of considering gender differences when analysing the impact of GPV on ITB and suggest that strategies to enhance ITB may need to be tailored differently for males and females.